All the rage : mothers, fathers, and the myth of equal partnership - Lockman, Darcy, 1972- (Harper, an imprint of HarperCollins Publishers, 2019)
Examines why parental work is still largely performed by women regardless of profession or class, drawing on a range of expert insights to identify three sources of unequal labor division in parenting.